Sensitive Spectrophotometric Method for Quantitation of Guaifenesin and Dropropizine in Their Dosage Forms - Ola M. Abdallah (International Journal of Analytical Chemistry)
Guaifenesin and dropropizine were analyzed through oxidation with periodic acid to give formaldehyde which was allowed to condense with 4-Amino-5-hydrazino-4H [1,2,4]-triazole-3-thiol (AHTT). The condensation product was further oxidized to yield a purple colored compound with maximum absorption at 550 nm. Beer's law was obeyed in the range of 5–45 𝜇g mL−1 for guaifenesin and 10–80 𝜇g mL−1 for dropropizine. Both drugs were also successfully determined in their dosage forms.